2019
DOI: 10.3906/kim-1806-32
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of 1,2-ethylene-bis(para-methylpyridinium) dichromate as a new selective and mild agent in oxidation of alcohols

Abstract: 1,2-Ethylene-bis(para-methyl pyridinium) dichromate, (C 14 H 18 N 2) [Cr 2 O 7 ], is used as a new oxidizing agent in conversion of some alcohols to their corresponding carbonyl compounds in CH 3 CN solvent and also under solvent-free conditions. In both procedures, high conversion percentages are observed. However, a much shorter reaction time is achieved in solvent-free conditions. For allylic alcohols, the C = C bond is not oxidized and the examined saturated alcohol in this work (i.e. cyclo-hexanol) remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The product (57.5 mg, 82% isolated yield) was isolated by eluant EtOAc/PE (1:9) as yellow liquid. The spectra match the reported literature [3] . Compound 2d was prepared following the standard procedure B.…”
Section: -Chlorobenzaldehydesupporting
confidence: 89%
See 1 more Smart Citation
“…The product (57.5 mg, 82% isolated yield) was isolated by eluant EtOAc/PE (1:9) as yellow liquid. The spectra match the reported literature [3] . Compound 2d was prepared following the standard procedure B.…”
Section: -Chlorobenzaldehydesupporting
confidence: 89%
“…1 But, most of them are limited for phenylacetic acid or α-hydroxyphenylacetic acid type substrates as phenyl group could greatly stabilize the intermediate generated from the decarboxylation process. On the other hand, with the rapid development of photocatalytic decarboxylative reactions, a wide range of α-amino, α-oxy, benzylic, and even simple alkyl radicals could be generated from carboxylic acids and used for further transformations, such as decarboxylative fluorinations, 2 vinylations, 3 alkynylations, 4 hydrodecarboxylation, 5 hydroxylation, 6 conjugate additions 7 and radical−radical coupling reactions. 8 Despite these seminal studies, few photocatalytic decarboxylative oxidations have been reported (Figure 1).…”
Section: Introductionmentioning
confidence: 99%